Analisis Efisiensi Teknis Sapi Potong di Kabupaten Kupang Provinsi Nusa Tenggara Timur - Mardit Nikodemus Nalle (Fakultas Pertanian, Universitas Timor, 2016)
The purpose of this research is to analysis technical efficiency of beef cattle productivity in Kupang Regency-East Nusa Tenggara. The Method of this research was purposed sampling with 76 respondents for the sample in Nonbes Subdistrict, Ponain Village, Kotabes Village, and Tesbatan Village. The result showed that the productivity of feedlot fattening was affected by initial weight, feed, vitamins, distilled water whereas labor force and medicine was affecting feedlot fattening. The value of Σβi is 0,978 (decreasing return to scale). The value of gamma showed that 40,62 percent feedlot fattening has been affected by internal factor whereas 59,38 percent has been affected by external factors (climate and disease).